PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI, KUALITAS SUMBER DAYA MANUSIA, PENGENDALIAN INTERN DAN KOMITEMEN ORGANISASI TERHADAP KETERANDALAN PELAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada Organisasi Perangkat Daerah Kabupaten Rokan Hilir) - Dedi Irawan; Novita Indrawati; Adhitya Agri Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research was to identify and analyze about The Effect Of Information Technology Utilization, Human Resources Quality, Acounting Internal Control and Comitmen Organisation to the reliability of financial reporting. This study was conducted in OPD Rokan Hilir. Data used in this research is primary data with questionnaire as instrument. The method used in sample selection is sensus sampling. The number of samples in this study was 81 respondents. Hypothesis test used in this research is statistical t test. Data analysis technique used in this research is multiple linear analysis using Statistical product and service solution (SPSS) version 20.0. The results show that Information Technology Utilization, Human Resources Quality, Acounting Internal Control and Comitmen Organisation have a positive effect to the reliability of financial reporting.Keywords : Information Technology Utilization, Human Resources Quality, Acounting Internal Control,Comitmen Organisation, reliability offinancialreporting.